Catabolic N2-acetylornithine 5-aminotransferase of Klebsiella aerogenes: control of synthesis by induction, catabolite repression, and activation by glutamine synthetase. - Friedrich, B (1978)
Klebsiella aerogenes formed two N2-acetylornithine 5-aminotransferases (ACOAT) which were separable by diethylaminoethyl-cellulose chromatography. One ACOAT was repressed when the cells grew on arginine-containing medium, indicating its function in arginine biosynthesis. The second ACOAT was induced when arginine or ornithine was present in the medium as the sole source of carbon or nitrogen, suggesting its function in the catabolism of these compounds. The induced enzyme was purified almost to homogeneity. Its molecular weight is 59,000; it is a pyridoxal 5-phosphate-dependent enzyme and exhibits activity with N2-acetylornithine (Km = 1.1 mM) as well as with ornithine (Km = 5.4 mM). ACOAT did not catalyze the transamination of putrescine or 4-aminobutyrate. The best amino acceptor was 2-ketoglutarate (Km = 0.7 mM). ACOAT formation was subject to catabolite repression exerted by glucose when ammonia was present in excess. When the cells were deprived of nitrogen, ACOAT escaped from catabolite repression. This activation was mediated by glutamine synthetase as shown by the fact that mutants affected in the regulation or synthesis of glutamine synthetase were also affected in the control of ACOAT formation.